Role of conductive nitrogen incorporated diamond nanowires for enhancing the UV detection and field emission properties of ZnO nanotubes. (15th September 2018) - Huang, Bohr-Ran; Saravanan, Adhimoorthy; Kathiravan, Deepa; Liou, Ruei-Hong; Keiser, Gerd
Abstract: In this study, we focus on the preparation of a nanocarbon and ZnO based hybrid with the incorporation of nitrogen to form diamond nanowires (N-DNW) and ZnO nanotubes (ZNTs) using simple routes. The potential of the carbon enriched hybrid material for application as UV photodetectors (PDs) or electron field emitters (EFE) is evaluated. Firstly, the ZNT/N-DNW based UV PDs with their multifinger anode cathode configuration offer a high photoresponse ratio of 1930, which is superior to that of bare ZnO PDs (12.6). The obtained photoresponse values also have greatly enhanced stability and photoresponsivity of 49.2 AW −1 compared with the ZNRs (0.4 AW −1 ). In addition, EFE study of the ZNT/N-DNW hybrid device reveals an electron emission at voltage as low as 2.59 V/μm with a high current density of 5.2 mA/cm 2 . This striking improvement in the multifunctional measurements of the annealed ZNT/N-DNW - based device can be attributed to its fast adsorptivity and oxygen vacancies. Moreover, the respective band model of this hybrid structure was also proposed to demonstrate its heterostructure. Furthermore, the outstanding feature of this combination are its cost-effective synthesis routes, reliability, and long-term stability, which makes it a potential applicant for multifunctional opto-electronic devices. Graphical abstract: Unlabelled Image Highlights: Weak stability of ZnO nanotubes (ZNTs) requires a suitable combination. Diamond nanowires (DNW) could be afford high adsorptivity and robustness to ZNTs. The integration of DNW enhanced the UV detection and Field emission properties of ZNTs. The interface of ZNTs/DNW n-N junction has been confirmed to play a vital role.